2021
DOI: 10.4081/aiua.2021.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Novel hormonal agents for metastatic Castration-Resistant Prostate Cancer: comparing outcomes. A single-center retrospective study

Abstract: Introduction: Prostate cancer is the most common cancer in men, accounting for 15% of all diagnosed cancers and is the sixth leading cause of cancerrelated deaths amongst men worldwide. Abiraterone and enzalutamide were the first two novel hormonal agents approved for the treatment of metastatic prostate cancer but there is a lack of quality evidence regarding which is associated with better outcomes and who would benefit the most with one or another of these drugs. Objective: To evaluate the clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…Better mCRPC response to ENZ was widely observed, although concomitant survival benefit was only occasionally found. Jarimba et al demonstrated higher response rates with ENZ versus AA (77.1% vs. 58.1%, p = 0.016) and showed that positive response independently reduced risk of both biochemical progression (OR: 0.248, p = 0.017) and death (OR: 0.302, p = 0.038), but still found no significant difference in all-cause time to death (37.5 months ENZ vs. 26 months AA, p = 0.277) [ 2 ]. Higher PSA response with ENZ (61.6% vs. 43.8%, p < 0.004) and greater time to progression (HR 0.66; 95% CI 0.50–0.88, p < 0.01) were recorded by Soleimani et al [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Better mCRPC response to ENZ was widely observed, although concomitant survival benefit was only occasionally found. Jarimba et al demonstrated higher response rates with ENZ versus AA (77.1% vs. 58.1%, p = 0.016) and showed that positive response independently reduced risk of both biochemical progression (OR: 0.248, p = 0.017) and death (OR: 0.302, p = 0.038), but still found no significant difference in all-cause time to death (37.5 months ENZ vs. 26 months AA, p = 0.277) [ 2 ]. Higher PSA response with ENZ (61.6% vs. 43.8%, p < 0.004) and greater time to progression (HR 0.66; 95% CI 0.50–0.88, p < 0.01) were recorded by Soleimani et al [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed included articles to uncover trends in ADEs and differences in common types of toxicities between AA and ENZ, along with associations with patient co-morbidities. Jarimba et al reported ADEs in 16.1% of AA and 11.4% of ENZ patients, while Chowdhury et al found that 7.1% of AA and 13.5% of ENZ patients discontinued treatment due to toxicity, and death during the treatment period was seen in 7.2% of AA and 11.1% of ENZ patients [ 2 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations